L’agriculture ouagalaise (Burkina Faso) comme modèle de contribution au métabolisme urbain : avantages et limites - Amélie Robert (Éditions en environnement VertigO, 2018)
Like many large African cities, Ouagadougou knows an increase of its cultivated areas. But they strongly depend on water and soil resources. How agriculture fits into and holds in the city ? What is its role ? In the framework of a research program, we took an interest in the relationship between the agriculture and the city of Ouagadougou, questioning the role of the first one in the sanitization of the second one. We conducted observations and field surveys in two spots of market gardening, the main kind of urban agriculture. We associated them with interviews of public officials and some Ouagalese we met in the spots. The first results show that agriculture is an essential activity for the city. It is at the heart of an important economic and social sector and it also plays a key role in sanitization, by the re-use of waste water and wastes. Thus, it strongly contributes to the urban metabolism and it proves precursory when, in northern countries, we think about solutions to privilege a functioning of the city in full circle. In Ouagadougou, it is not a product of an organized willingness : the authorities doom the urban agriculture. They raise negative elements : they denounce the environmental pollutions generated and the public health problems, which are linked to the use of waste water and wastes. These problems are well real and they limit the scope of this model as agriculture contribution to the urban metabolism.